Strengthening social literacy among elementary students through the integration of sdgs into social studies instruction - Ani Rosidah; Indani Damayanti; Siti Zazak Soraya (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study examines the integration of Sustainable Development Goals (SDGs) values into Social Studies learning in elementary schools and its relation to the development of students’ social literacy. The research was conducted in three public elementary schools and involved twelve participants, consisting of three principals, six teachers, and three students. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews, and document analysis. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that SDG values were integrated into Social Studies through (1) contextual discussions of local socio-environmental issues, (2) participatory learning activities such as group investigations and collaborative projects, and (3) guided critical reflection sessions. This integration was reflected in observable indicators of social literacy, including students’ ability to identify social and environmental problems in their surroundings, express reasoned opinions during classroom discussions, and participate in school-based environmental initiatives. The study contributes to a contextual description of SDGs integration practices in elementary Social Studies and clarifies their linkage to specific dimensions of students’ social literacy development.